2023
DOI: 10.2147/bctt.s415432
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Treatment Outcomes Between Patients with HER2-Low versus HER2-Zero, Hormone Receptor-Positive Advanced-Stage Breast Cancer Treated with Ribociclib

Abstract: Background Metastatic breast cancers (MBC) with no expression of human epidermal growth factor receptor-2 (HER2) are recently classified into two groups; HER2-zero [HER2-immunohistochemistry (IHC) score of 0 (IHC-0)] and HER2-low, defined as those with IHC score of 1+ or 2+ with negative in situ hybridization (ISH) assay. We investigate differences in treatment outcomes between both groups treated with endocrine therapy (ET) and the CDK4/6 inhibitor ribociclib. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…While the predictive role of HER2-low status on ET response is not firmly established, our data suggest that HR+/HER2−low MBC may derive less benefit from ET than HR+/HER2−zero MBC. Recent retrospective studies also reported consistent results suggesting bidirectional crosstalk between the HR and HER2 pathways as a potential mechanism of hormonal resistance and poor outcomes [36,37].…”
Section: Discussionmentioning
confidence: 67%
“…While the predictive role of HER2-low status on ET response is not firmly established, our data suggest that HR+/HER2−low MBC may derive less benefit from ET than HR+/HER2−zero MBC. Recent retrospective studies also reported consistent results suggesting bidirectional crosstalk between the HR and HER2 pathways as a potential mechanism of hormonal resistance and poor outcomes [36,37].…”
Section: Discussionmentioning
confidence: 67%
“…Nine studies encompassing a total of 2705 patients were included in the analyses. The four studies were conducted in the first line [ 18 , 23 25 ], while mixed cohorts were present in five studies [ 17 , 19 , 26 28 ]. Five studies were multicenter, and single-center data were reported in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effects of low-level HER2 expression on the survival are yet to be defined [ 15 , 16 ]. While some studies reported inferior survival in patients with HR+HER2-low tumors, several studies stated similar survival in HER2-low and HER2-zero tumors [ 17 – 19 ]. In addition to the prognosis, the low levels of HER2 expression could affect the efficacy of anti-endocrine agents, including the CDK 4/6 inhibitors, due to the pivotal role of the ErbB2 receptor on endocrine resistance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 However, HER2 negative levels can affect the treatment results of patients with HER2-zero who have low response rates and the better progression-free survival (PFS) compared with patients with HER2-low disease; therefore, studies with larger samples are recommended that can help oncologists select HER2-low patients for better treatment options. 5 …”
Section: Dear Editormentioning
confidence: 99%